TUNGSTEN GEOCHEMISTRY IN INTRUSIVE COMPLEXES OF THE PAMIRS AND SOUTHERN TIEN SHAN (TAJIKISTAN) - Mogarovskii V.V. (My University, 2001)
The tungsten distribution in intrusive rocks of the region was studied based on analysis of ~250 composite samples combined from more than 900 individual samples. The average W content in the Paleozoic granites and granodiorites of the Northern Pamirs is three times lower (0.7 ppm) than the global average (clarke value) in such rocks according to A.A. Beus. The weighted average of W concentrations in the Southern Tien Shan granitic rocks is much higher (2.6 ppm). Average W content in Mesozoic-Cenozoic igneous rocks (muscovite and biotite-muscovite granites) of the Southern Pamirs is estimated at 3.7 ppm. Mesozoic-Cenozoic alkali basaltoids of this region are also slightly enriched in this element (4-7 ppm in the Southern Pamirs and 14 ppm on the average in the Neogene rocks). The analogous rocks of the Southern Tien Shan contain up to 2-5 ppm W. Tungsten (mainly scheelite) mineralization is abundant in the Southern Tien Shan and locally occurs in the Southern Pamirs.
Keywords: Mesozoic; Cenozoic; Paleozoic; Neogene; Кайнозой; Paleozoic; Кайнозой::Неоген; Cenozoic::Neogene; Мезозой; Палеозой; Mesozoic; Cenozoic